Atmospheric circulation and features of distribution of anomalies of temperature and preciptation in Kazakhstan. (Journal of Geography and Environmental Management, 2016)
The fields of air temperature anomalies and precipitation in Kazakhstan, characteristic for the basic forms of atmospheric circulation W, C and Е are considered in the article.